Purification and characterization of a soluble glycoprotein from garlic (Allium sativum) and its in vitro bioactivity. Issue 7 (2nd October 2016) - Wang, Yan; Zou, Tingting; Xiang, Minghui; Jin, Chenzhong; Zhang, Xuejiao; Chen, Yong; Jiang, Qiuqing; Hu, Yihong
ABSTRACT: A soluble glycoprotein was purified to homogeneity from ripe garlic ( Allium sativum ) bulbs using ammonium sulfate precipitation, Sephadex G-100 gel filtration, and diethylaminoethyl-52 cellulose anion-exchange chromatography. A native mass of 55.7 kDa estimated on gel permeation chromatography and a molecular weight of 13.2 kDa observed on sodium dodecyl sulfate-polyacrylamide gel electrophoresis supported that the glycoprotein is a homotetramer. β -Elimination reaction result suggested that the glycoprotein is an N -linked type. Fourier-transform infrared spectroscopy proved that it contains sugar. Gas chromatography–mass spectrometer analysis showed that its sugar component was galactose. The glycoprotein has 1, 1-diphenyl-2-picrylhydrazil free radical scavenging activity and the peroxidation inhibition ability to polyunsaturated fatty acid. These results indicated that the glycoprotein has potential for food additives, functional foods, and even biotechnological and medical applications.